1972
DOI: 10.1111/j.1432-1033.1972.tb01999.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Protein Properties by Change in Charge

Abstract: Succinylated derivatives of bovine chymotrypsinogen A and n-chymotrypsin were prepared by treatment of the native proteins with succinic anhydride; 60°/, of the 6-amino groups of the 13 lysine residues form stable succinylated products. The large negative charge a t neutral pH is reflected in electrophoretic and titration behavior but absorption spectra, rotatory-dispersion spectra and reversible unfolding behavior indicate that the succinylated species are conformationally similar to the parent proteins. Succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1973
1973
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…The rapid rise in extent of coupling after dialysis and lyophilization probably involves conformational changes in the protein due to reversible dissociation of succinyl groups during dialysis or to lyophilization, rather than to the mere addition of fresh reagent. A similar effect has been reported for succinylation of chymotrypsinogen (21).…”
Section: Discussionsupporting
confidence: 60%
“…The rapid rise in extent of coupling after dialysis and lyophilization probably involves conformational changes in the protein due to reversible dissociation of succinyl groups during dialysis or to lyophilization, rather than to the mere addition of fresh reagent. A similar effect has been reported for succinylation of chymotrypsinogen (21).…”
Section: Discussionsupporting
confidence: 60%
“…Tables 3 and 4 present the phase-diagram data for the two two-phase systems studied. The proteins studied here are well characterized with respect to surface charge as a function of pH (Tanford and Wagner, 1954;Tanford et al, 1955;Sakakibara and Hamaguchi, 1968;Shiao et al, 1972;Horn and Heuck, 1983). As stated above, chlorides and sulfates added to the phase systems do not alter the pH of the phases significantly from neutral pH; however, the pH of 50 mM potassium phosphate is 5.5.…”
Section: Resultsmentioning
confidence: 98%
“…The dispersion energy parameter ε 1 /k B for α-chymotrypsin is regressed from the osmotic pressure data of Haynes et al [2], and has a value of 466.32 K. We regard the molecular weight and dispersion energy parameter ε 1 /k B for a specific protein as constants when pH and ionic strength in solutions are changed. The used net charge of α-chymotrypsin molecule is the titration data of Marini and Wunsch [22], and Shiao et al [23], which can be found in Table 2.…”
Section: α-Chymotrypsin Solutionsmentioning
confidence: 99%